A long-period superlattice phase in Mg97Zn1Yb2 alloys synthesized under high-pressure. (August 2016) - Matsushita, Masafumi; Inugai, Ryota; Yamasaki, Michiaki; Shinmei, Toru; Kawamura, Yoshihito; Irifune, Tetsuo; Fujita, Naoya; Abe, Eiji
Abstract: A novel long-period superlattice Mg77 Zn9 Yb14 phase, whose dimensions are described as √ 3 × √ 3 × 3 with respect to the original hexagonal close-packed Mg lattice, has been found in Mg97 Zn1 Yb2 alloys synthesized under high pressure (5 GPa) and at high temperature (723 K). A preliminary model structure is constructed based on atomic-resolution electron microscopy and first-principles calculations, providing local configurations around Yb atoms whose sizes appear to be smaller than those of a divalent Yb. This may be reasonably attributed to an applied high-pressure effect. Graphical abstract: A novel long-period superlattice (LPSL) Mg77 Zn9 Yb14 phase.